Survey of Plant Diseases in Horticultural Crops in Cheorwon, South Korea, in 2024 - Bae, Miah; Kim, Namsuk; Ju, Sangyeon; Kim, Byungyeon; Gu, Hyunmo; Kim, MeeKyoung; Park, Mi-Ri (Sigmulbyeong yeon'gu, 2025)
A field survey was conducted from January to October 2024 to investigate the occurrence of plant diseases caused by fungal, bacterial, and viral pathogens in major horticultural crops cultivated in Cheorwon-gun, Gangwon-do, South Korea. Eight representative crops, including paprika and tomato, were examined using specific primers for pathogenic microorganisms via polymerase chain reaction (PCR) and reverse transcription PCR (RT-PCR). As a result, five fungal pathogens were detected: Botrytis cinerea, Fusarium oxysporum, Phytophthora capsici, P. infestans, and Pythium ultimum. Among them, P. ultimum and P. infestans were predominant, each accounting for 40% of the total fungal detections, jointly representing 80.00% of all fungal cases. Three bacterial pathogens were identified: Clavibacter michiganensis, Pectobacterium carotovorum, and Ralstonia solanacearum, with R. solanacearum showing the highest incidence (75%). Seven viral pathogens were also detected, including broad bean wilt virus 2, cucumber green mottle mosaic virus, cucumber mosaic virus, pepper mottle virus, pepper mild mottle virus, tomato spotted wilt virus (TSWV), and watermelon mosaic virus, with TSWV being the most prevalent (64.86%). Spatial analysis showed that R. solanacearum and TSWV were found across all six surveyed regions of Cheorwon-gun, indicating widespread distribution. Seasonal patterns revealed that fungal diseases were most prevalent in May, bacterial diseases peaked during July and August, and viral infections were primarily detected between May and July. These findings provide baseline data for the development of effective disease monitoring and management strategies in horticultural crop production in Cheorwon-gun.